Preparation method of high-wear-resistant polyester functional fabric
Patent Information
- Application Number
- CN202611250045.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-18
- Publication Date
- 2026-10-27
AI Technical Summary
[0006]综上,现有技术存在以下两项核心缺陷:其一,均聚对苯二甲酸乙二酯纱线作为基础材料,导致耐磨性与多功能性在纤维本体层面产生不可调和的性能拮抗,无法同时实现高耐磨、高吸湿、抗静电等综合功能,其二,物理涂层整理方案因界面结合力不足,导致耐磨功能层耐久性差,且脱落碎片形成微塑料污染,目前尚无能够从纤维制备与后整理全链条上实现多功能集成、并从源头杜绝微塑料脱落的规模化技术方案,为此,我们提出一种高耐磨涤纶功能性面料的制备方法
[0018]1.本发明从根本上解决了性能拮抗矛盾,芯层高结晶度均聚对苯二甲酸乙二酯专司机械强度和本体耐磨性,皮层共聚改性聚对苯二甲酸乙二酯专司亲水、抗静电及共价键合功能化,实现了两类性能的空间解耦,芯层与皮层在同一纤维截面中协同发挥作用,互不干扰,彻底打破了传统工艺中耐磨性与多功能性之间的性能拮抗;
Smart Images

Figure CN122980071A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of functional textile manufacturing technology, specifically to a method for preparing a highly abrasion-resistant polyester functional fabric. Background Technology
[0002] Polyethylene terephthalate (PET) fiber is currently the world's largest synthetic fiber raw material. Due to its excellent mechanical strength, dimensional stability and chemical resistance, it occupies a dominant position in the fields of apparel, industrial and home textiles. The conventional preparation process of polyester fabric includes the following steps: preparation of PET polymer chips, melt spinning, stretching and setting, yarn processing, weaving and finishing.
[0003] In terms of improving wear resistance, there are two main types of solutions in the existing technology, and both types of solutions have fundamental defects.
[0004] The first approach is to increase the crystallinity of polyethylene terephthalate (PET) polymers. High-crystallinity PET fibers have highly regular molecular chains and strong abrasion resistance, but the chemical inertness of the fiber surface is significantly enhanced. They contain almost no reactive functional groups and are extremely hydrophobic, which leads to a sharp decline in the fiber's moisture absorption, antistatic properties, and dyeability. This results in an irreconcilable performance antagonism between high abrasion resistance and moisture absorption and antistatic multifunctionality, making it impossible to achieve the above properties in the same fiber structure.
[0005] The second category is physical coating finishing solutions, including polyurethane coating finishing and nanoparticle physical adsorption finishing. The polyurethane coating finishing solution applies water-based or solvent-based polyurethane to the fabric surface via blade coating or roller transfer, and then cures at 100–130°C to form a physically adhered abrasion-resistant film. The nanoparticle physical adsorption finishing solution prepares a finishing liquid by mixing reinforcing particles such as nano-silica with an adhesive, and then cures it by padding and baking at 120–140°C, allowing the nanoparticles to adhere to the fiber surface with the physical adhesion of the adhesive. In both of these solutions, the bonding force between the finishing agent and the polyethylene terephthalate fiber originates from van der Waals forces or physical anchoring, resulting in extremely low interfacial energy. Under the combined effects of shear stress generated by repeated mechanical friction, cyclic fatigue stress from the expansion and contraction of hot water during washing, and chemical erosion by detergents, the coating peels off over a large area. The fabric's abrasion resistance significantly decreases after 10–20 washes. Furthermore, the peeled polymer fragments and nanoparticles, as microplastics, enter natural water bodies with wastewater, posing a threat to aquatic life and human health.
[0006] In summary, existing technologies have the following two core defects: First, using homopolymer polyethylene terephthalate yarn as the base material results in an irreconcilable performance antagonism between abrasion resistance and multifunctionality at the fiber body level, making it impossible to simultaneously achieve comprehensive functions such as high abrasion resistance, high moisture absorption, and antistatic properties. Second, physical coating finishing schemes suffer from insufficient interfacial adhesion, leading to poor durability of the abrasion-resistant functional layer and the formation of microplastic pollution from detached fragments. Currently, there is no large-scale technical solution that can achieve multifunctional integration from the entire fiber preparation and finishing chain and eliminate microplastic detachment at the source. Therefore, we propose a method for preparing high abrasion-resistant polyester functional fabrics. Summary of the Invention
[0007] The purpose of this invention is to provide a method for preparing a highly abrasion-resistant polyester functional fabric.
[0008] To achieve the above objectives, the present invention provides the following technical solution: a method for preparing a high abrasion-resistant polyester functional fabric, comprising the following steps:
[0009] Raw material preparation steps: Homopolymer polyethylene terephthalate chips with an intrinsic viscosity of 0.80-0.95 dL / g are used as the core layer material, and copolymerized modified polyethylene terephthalate chips containing sodium sulfonate hydrophilic groups and polyethylene glycol soft segments are used as the skin layer material. The terminal hydroxyl content of the skin layer material is not less than 30 mmol / kg.
[0010] Composite spinning steps: A core-sheath type bicomponent composite melt spinning process is adopted. The core layer raw material and the sheath layer raw material are extruded separately through independent melt channels in a composite spinning assembly to form a core-shell structure composite polyester fiber with homopolymer polyethylene terephthalate as the core layer and copolymer-modified polyethylene terephthalate as the sheath layer. The core-sheath area ratio of the composite polyester fiber is... Defined as:
[0011] ;
[0012] in, The core-skin area ratio (dimensionless). This refers to the cross-sectional area of the cortex, in μm². This refers to the cross-sectional area of the core layer, in μm². The value range is 0.25 to 0.40, and the design principle for this ratio is: the cortex proportion is sufficiently thin ( To ensure that the highly crystalline polyethylene terephthalate in the core layer makes a dominant contribution to the overall mechanical properties of the fiber, and that the sheath layer is sufficiently thick ( This ensures that the functionalized copolymer layer is fully exposed on the fiber surface, providing sufficient reactive sites for post-treatment covalent bonding.
[0013] Weaving steps: The core-shell structured composite polyester fiber is woven into a greige fabric after yarn processing, and then refined to remove oil and impurities.
[0014] Low-temperature plasma pre-activation step: The refined fabric is surface-treated using an atmospheric pressure dielectric barrier discharge plasma device to introduce oxygen-containing active groups such as hydroxyl, carbonyl and carboxyl groups on the surface of the corrugated fiber, thereby increasing the density of reactive sites in the corrugated fiber.
[0015] In-situ covalent bonding finishing steps: The pre-activated fabric is impregnated with a finishing solution containing modified nano-silica with surface-grafted epoxy groups and polyetheramine. After pre-drying, it is baked at 150-170℃ for 3-5 minutes. At this temperature, two types of covalent bonding reactions occur: the epoxy groups on the surface of the modified nano-silica undergo a ring-opening addition reaction with the terminal hydroxyl groups on the surface of the corrugated fiber to form ether bonds covalently; the terminal primary amine group of the polyetheramine undergoes a dehydration condensation reaction with the terminal carboxyl group of the corrugated fiber to form amide bonds covalently. At the same time, the primary amine group at the other end of the polyetheramine undergoes a ring-opening reaction with the excess epoxy groups on the surface of the modified nano-silica to form carbon-nitrogen bonds. The two types of covalent bonding reactions work synergistically, with polyetheramine as a bridging molecule, to connect the modified nano-silica and the corrugated fiber in a double-end covalent bonding manner, and construct a dense three-dimensional cross-linked covalent network wear-resistant functional layer of fiber-polyetheramine-modified nano-silica on the surface of the fiber corrugated layer.
[0016] Washing and setting steps: The baked fabric is washed three times with hot water at 80℃ to remove unreacted free finishing agents and by-products, and then set at 170-180℃ to control the width and weight, thus obtaining the high abrasion-resistant polyester functional fabric.
[0017] Compared with the prior art, the beneficial effects of the present invention by adopting the above technical solution are as follows:
[0018] 1. This invention fundamentally solves the performance antagonism contradiction. The core layer of highly crystalline homopolymer polyethylene terephthalate is dedicated to mechanical strength and bulk wear resistance, while the skin layer of copolymerized modified polyethylene terephthalate is dedicated to hydrophilicity, antistatic properties, and covalent bonding functionalization. This achieves spatial decoupling of the two types of properties. The core layer and the skin layer work synergistically in the same fiber cross section without interfering with each other, completely breaking the performance antagonism between wear resistance and multifunctionality in traditional processes.
[0019] 2. This invention achieves long-lasting and durable abrasion resistance. The finishing layer is anchored to the fiber skin through covalent bonds with a bond energy of 200-400 kJ / mol, which is much higher than the van der Waals force of physical adsorption of 0.1-10 kJ / mol. After 50 standard household washes, the abrasion resistance retention rate is not less than 85%, and the durability is significantly better than physical coating finishing schemes.
[0020] 3. This invention significantly reduces microplastic emissions at the source. The wear-resistant functional layer is bonded by chemical covalent bonds and does not undergo macroscopic peeling under normal use and washing conditions. The amount of microplastics released into washing wastewater is reduced by no less than 70% compared to traditional physical coating solutions. This invention responds to domestic and international regulations on microplastic emission reduction in textiles and has significant environmental benefits.
[0021] 4. This invention endows the fabric with good moisture absorption and antistatic properties. The sodium sulfonate groups and polyethylene glycol soft segments introduced into the skin layer endow the fiber with permanent hydrophilic and antistatic functions. The introduction of polyetheramine further enhances the moisture absorption and wicking capacity. The fabric moisture regain and antistatic decay time indicators are significantly better than homopolymer polyethylene terephthalate fabric. Attached Figure Description
[0022] Figure 1 This is a complete overall process flow diagram in an embodiment of the present invention;
[0023] Figure 2 This is a schematic diagram of the segmented fiber preparation process in an embodiment of the present invention;
[0024] Figure 3 This is a schematic diagram of the post-composition covalent bonding process in an embodiment of the present invention. Detailed Implementation
[0025] The following is in conjunction with the appendix Figure 1-3 The specific embodiments of the present invention will be further described below. It should be noted that the description of these embodiments is for the purpose of helping to understand the present invention, but does not constitute a limitation of the present invention.
[0026] Furthermore, the technical features involved in the various embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other.
[0027] Example 1:
[0028] (a) Raw material preparation:
[0029] The core layer raw material is selected from homopolymer polyethylene terephthalate chips with an intrinsic viscosity of 0.88 dL / g, a crystallinity of not less than 45%, and a melting point of 260℃. The core layer chips are vacuum-dried before spinning at a temperature of 135℃ for 8 hours, and the moisture content is controlled below 25 ppm to prevent the decrease in molecular weight caused by the hydrolysis and degradation of polyethylene terephthalate during high-temperature melt spinning.
[0030] The preparation process of the skin layer raw material is as follows: using purified terephthalic acid and ethylene glycol as the main monomers, sodium dimethyl isophthalate-5-sulfonate (5 mol% relative to the molar weight of purified terephthalic acid) is added. In the presence of a titanium-based catalyst (0.04% of the mass of purified terephthalic acid), a transesterification reaction is carried out at 260℃ under nitrogen protection, allowing sodium dimethyl isophthalate-5-sulfonate to embed into the polyethylene terephthalate backbone, introducing hydrophilic groups from the sodium sulfonate. After the transesterification is complete, polyethylene glycol with a number average molecular weight of 1000 g / mol is added, in an amount equal to the copolymerized polyethylene terephthalate. At a theoretical yield of 6 wt%, the hydroxyl groups at both ends of polyethylene glycol (PEG) undergo a block copolymerization reaction with the hydroxyl groups at the ends of the polyethylene terephthalate (PET) backbone, forming a block copolymer in which PEG soft segments are embedded in the PET backbone. This imparts hydrophilicity and low-temperature flexibility to the skin material. Subsequently, melt polycondensation is carried out under an absolute pressure of 80 Pa and a temperature of 280 °C until the intrinsic viscosity of the copolymer PET reaches 0.63 dL / g and the hydroxyl content at the ends is 38 mmol / kg, which meets the requirements for the density of active sites in subsequent covalent bonding pairs. The copolymer PET chips are then underwater pelletized and dried for later use.
[0031] (II) Core-shell composite spinning and yarn processing:
[0032] A core-skin type bicomponent composite melt spinning process is adopted. The core layer homopolymer polyethylene terephthalate chips are melted in a single-screw extruder, and the temperature gradient of each zone is set as follows: feeding section 265℃, compression section 275℃, metering section 285℃, and spinning box 290℃. The skin layer functionalized copolymer polyethylene terephthalate chips are melted in an independent single-screw extruder, and the spinning box temperature is set at 278℃, which is 12℃ lower than that of the core layer, in order to adapt to the low melting point of copolymer polyethylene terephthalate (melting point of about 248℃) and prevent the copolymer from thermally degrading and the sulfonic acid groups from thermally decomposing.
[0033] After being precisely metered by two metering pumps, the two melt streams enter the core and sheath channels of the composite spinning assembly, respectively, and are then extruded together at the spinning orifice. The ratio of the sheath cross-sectional area to the core cross-sectional area is controlled by adjusting the speed ratio of the sheath metering pump to the core metering pump. With a value of 0.30, the corresponding skin layer thickness accounts for approximately 22% of the fiber diameter, ensuring both the dominant contribution of the highly crystalline polyethylene terephthalate in the core layer to the overall mechanical properties of the fiber and ensuring that the functionalized copolymer layer is fully exposed on the outer surface of the fiber.
[0034] Nascent fibers are wound at a spinning speed of 1200 m / min, then drawn by hot rollers. The pre-drawing roller temperature is 85℃, the main drawing roller temperature is 135℃, the total draw ratio is 3.8 times, the heat setting temperature is 205℃, and the setting time is 0.8s, to obtain a core-sheath composite polyester filament with a specification of 100 dtex / 48f and a single filament linear density of approximately 2.1 dtex. The composite filament is then subjected to false twist texturing (texturing temperature 180℃) to produce elastic yarn for subsequent weaving.
[0035] (III) Fabric weaving:
[0036] Using a rapier loom, the above-mentioned core-shell composite polyester elastic yarn is used as warp and weft yarns to weave a 3 / 1 twill fabric. The designed weight of the finished fabric is 260 g / m². Because the weft point float is longer, the surface abrasion resistance of the twill fabric is better than that of the plain weave, making it the preferred weaving structure of this invention. The fabric is scourted in an 80°C alkaline scouring solution to remove spinning oil and impurities introduced during the weaving process. After scouring, it is thoroughly washed and dried for finishing treatment.
[0037] (iv) Preparation of modified nano-silica and finishing solution:
[0038] Surface modification of nano-silica: Take fumed silica with a particle size of 20 nm, add anhydrous ethanol to prepare a dispersion with a mass fraction of 5%, and ultrasonically disperse for 30 min (ultrasonic frequency 20 kHz, power 300 W). Add 3-glycidyl etheroxypropyltrimethoxysilane, the amount of which is 8 wt% of the mass of fumed silica. Stir and hydrolyze the grafting in a 60℃ water bath for 4 hours to allow the methoxy group of 3-glycidyl etheroxypropyltrimethoxysilane to undergo a condensation and de-alcoholization reaction with the silanol group on the surface of nano-silica, and graft epoxy groups onto the surface of nano-silica to obtain modified nano-silica with a surface rich in epoxy groups, which is denoted as epoxy-modified nano-silica.
[0039] Preparation of finishing solution: Add 3 wt% of epoxy-modified nano-silica (based on unmodified silica) to deionized water, sonicate for 20 min, add 5 wt% of polyetheramine with a number average molecular weight of 1000 g / mol, add glacial acetic acid to adjust the pH of the finishing solution to 6.0, add 0.8 wt% of nonionic penetrant, stir the finishing solution thoroughly before use, and use immediately.
[0040] (v) Low-temperature plasma pre-activation:
[0041] The refined fabric is pre-activated on the surface using an atmospheric pressure dielectric barrier discharge plasma device. The discharge gas is air, the power density is 20W / cm², the treatment time is 60s, and the treatment temperature is room temperature (30℃). After plasma bombardment, the surface of the corrugated fiber undergoes oxidation etching, generating oxygen-containing active groups such as hydroxyl, carbonyl, and carboxyl groups. The concentration of oxygen-containing functional groups (characterized by X-ray photoelectron spectroscopy) is significantly increased, and the hydroxyl peak area increases by about 45%, providing sufficient and uniformly distributed active sites for subsequent covalent bonding reactions. After the plasma pre-activation treatment, the fabric must enter the padding process within 20 minutes to prevent the surface active groups from being quenched and decayed.
[0042] (vi) Padding-baking covalent bonding finishing:
[0043] The plasma-activated fabric is immediately immersed in the finishing solution padding tank and treated with a two-dip, two-roll process. The roll allowance is controlled at 70%, the roll pressure is 0.4 MPa, and the finishing solution temperature is 30℃ (room temperature padding to prevent the epoxy groups in the finishing solution from self-polymerizing and failing at high temperatures).
[0044] After padding, the fabric is placed in a pre-drying oven and dried at 90°C for 4 minutes to remove most of the free moisture. At the same time, the finishing agent is allowed to fully contact and migrate to the fiber surface, creating favorable conditions for covalent bonding.
[0045] After pre-drying, the fabric is placed in a high-temperature baking oven and baked at 160°C for 4 minutes. Under this temperature and weakly acidic environment, the following two types of core covalent bonding reactions occur:
[0046] Reaction type A is a ring-opening addition reaction between epoxy groups and terminal hydroxyl groups. The epoxy groups grafted onto the surface of epoxy-modified nano silica through a silane coupling agent undergo ring-opening addition with the terminal hydroxyl groups on the surface of the corrugated polyethylene terephthalate fiber under high temperature and weak acid catalysis, forming ether bonds (carbon-oxygen-carbon covalent linkage), which firmly anchor the modified nano silica system to the surface of the fiber corrugated layer.
[0047] Reaction type B is a double-end covalent bonding reaction of polyetheramine. One end of the primary amine terminal reacts with the epoxy group on the surface of epoxy-modified nano silica to form a carbon-nitrogen bond through a ring-opening reaction. The other end of the primary amine terminal reacts with the terminal carboxyl group of the corrugated fiber through dehydration condensation at high temperature to form an amide bond. As a flexible bridging molecule, polyetheramine connects the modified nano silica and the corrugated fiber through double-end covalent bonding, forming a dense three-dimensional cross-linked covalent network wear-resistant functional layer of fiber-polyetheramine-modified nano silica on the surface of the fiber corrugated layer. The structural integrity is far superior to that of traditional physical coatings.
[0048] (vii) Washing and setting:
[0049] After baking, the fabric is washed three times with hot water at 80℃ to fully remove unreacted free finishing agents, by-products and hydrolysis products. Finally, it is set at 175℃ by a setting machine to control the width and weight, and the final product is a high abrasion-resistant polyester functional fabric.
[0050] Performance testing:
[0051] The high abrasion-resistant polyester functional fabric prepared in Example 1 was subjected to the following performance tests: Abrasion resistance was tested using the Martindale method. After 50 standard household washes (according to AATCC 61-2A method), the fabric retained 92% of its abrasion resistance. The moisture regain was measured according to national standards, and the fabric had a moisture regain of 2.8%, which was significantly better than the 0.4% of the homopolymer polyethylene terephthalate fabric. The amount of microplastics released in the washing wastewater was reduced by 76% compared to the traditional physical polyurethane coating scheme. The antistatic decay time of the fabric was better than that of the homopolymer polyethylene terephthalate fabric of the same specification. The combined moisture absorption and antistatic properties met the requirements for use as a functional apparel fabric.
[0052] Example 2:
[0053] The main difference between Example 2 and Example 1 is that in the finishing step after in-situ covalent bonding, the epoxy-modified nano-silica in the finishing solution is replaced with isocyanate-modified nano-silica. Specifically, 3-isocyanate-propyltrimethoxysilane (8 wt% of the mass of fumed silica) is used to perform surface grafting modification on fumed silica with a particle size of 20 nm. The modification method is similar to the nano-silica surface modification step in Example 1, and surface-grafted isocyanate-modified nano-silica is obtained. Since isocyanate groups are prone to self-polymerization and deactivation when exposed to moisture, the finishing solution must be prepared and used immediately in a low humidity environment with a relative humidity of less than 40%, and the storage time should not exceed 4 hours. The remaining components and amounts of the finishing solution are the same as in Example 1.
[0054] The high-temperature baking temperature was adjusted to 150℃ and the baking time was 4 minutes. At this temperature, the isocyanate groups and the terminal hydroxyl groups on the surface of the corrugated fiber undergo a urethane reaction to generate urethane bonds (oxygen-carbon-nitrogen covalently linked). The modified nano-silica system is anchored to the surface of the fiber corrugated layer by covalent bonds. The covalent bond energy is comparable to that of the epoxy ring-opening product in Example 1. The remaining steps, such as plasma pre-activation, padding, pre-drying, and water washing and shaping, are exactly the same as in Example 1.
[0055] The fabric prepared in Example 2 was subjected to performance testing: after 50 standard household washes, the abrasion resistance retention rate reached 89%, the release of microplastics in the washing wastewater was reduced by 73% compared with the traditional physical coating scheme, and the fabric moisture regain rate was 2.6%. Example 2 proved the technical feasibility of using isocyanate-based silane coupling agents to replace epoxy-based silane coupling agents as modified nano-silica surface active groups to achieve covalent bonding abrasion-resistant finishing. Compared with Example 1, the baking temperature of Example 2 was slightly lower, and the energy consumption was relatively reduced, but the requirements for the preparation and storage conditions of the finishing solution were more stringent.
[0056] Example 3:
[0057] Example 3 differs from Example 1 in the composition of the leather material. In the preparation of the leather material, the amount of sodium dimethyl isophthalate-5-sulfonate introduced was adjusted to 3 mol%, the number-average molecular weight of polyethylene glycol was adjusted to 600 g / mol, and the amount added was 8 wt%. After melt polycondensation, the intrinsic viscosity of the leather material was 0.68 dL / g, the terminal hydroxyl content was 32 mmol / kg, and the core-sheath area ratio in the composite spinning was... The ratio was adjusted to 0.25, which further reduced the proportion of the cortex, thereby increasing the contribution of the homopolymer polyethylene terephthalate in the core layer to the mechanical properties of the fiber. The weaving adopted a plain weave structure, and the finished weight was 200 g / m². In the finishing process, the plasma treatment power density was increased to 28 W / cm², and the treatment time was extended to 100 s to compensate for the insufficient density of active sites when the cortex was relatively thin. The amount of epoxy-modified nano-silica in the finishing solution was increased to 4 wt%, the amount of polyetheramine was increased to 6 wt%, and the baking temperature was 165 ℃ for 4 min.
[0058] The fabric prepared in Example 3 was subjected to performance testing: after 50 standard household washes, the abrasion resistance retention rate reached 90%, the release of microplastics in the washing wastewater was reduced by 74% compared with the traditional physical coating scheme, and the fabric moisture regain rate was 2.2%. Example 3 verified that when the core-sheath area ratio is taken to the lower limit, by increasing the intensity of plasma treatment and the amount of active components in the finishing solution, the covalent bonding efficiency can be effectively maintained, ensuring the bonding strength of the abrasion-resistant functional layer.
[0059] Although the present invention has been disclosed above with reference to preferred embodiments, it is not intended to limit the present invention. Any person skilled in the art can make possible changes and modifications without departing from the spirit and scope of the present invention. Therefore, any modifications, equivalent changes and alterations made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention shall fall within the protection scope defined by the claims of the present invention.
Claims
1. A method for preparing a high abrasion-resistant polyester functional fabric, characterized in that: Includes the following steps: Raw material preparation steps: Homopolymer polyethylene terephthalate chips with an intrinsic viscosity of 0.80-0.95 dL / g are used as the core layer material, and copolymerized modified polyethylene terephthalate chips containing sodium sulfonate hydrophilic groups and polyethylene glycol soft segments are used as the skin layer material. The terminal hydroxyl content of the skin layer material is not less than 30 mmol / kg. Composite spinning steps: A core-sheath type bicomponent composite melt spinning process is adopted, in which the core layer raw material and the sheath raw material are extruded separately through independent melt channels in a composite spinning assembly to form a core-shell structure composite polyester fiber with homopolymer polyethylene terephthalate as the core layer and copolymer-modified polyethylene terephthalate as the sheath layer. The ratio of the cross-sectional area of the sheath layer to the cross-sectional area of the core layer of the composite polyester fiber is 0.25 to 0.
40. Weaving steps: The core-shell structured composite polyester fiber is woven into a greige fabric after yarn processing, and then refined. Low-temperature plasma pre-activation step: The refined fabric is surface-treated using an atmospheric pressure dielectric barrier discharge plasma device to introduce oxygen-containing active groups on the surface of the corrugated fibers. In-situ covalent bonding finishing steps: The pre-activated fabric is impregnated with a finishing solution containing modified nano-silica with surface-grafted epoxy groups and polyetheramine. After pre-drying, it is baked at 150-170℃ for 3-5 minutes, so that the epoxy groups on the surface of the modified nano-silica and the terminal hydroxyl groups on the surface of the sheath fiber undergo a ring-opening addition reaction to form ether bonds covalently. At the same time, the terminal primary amine group of the polyetheramine and the terminal carboxyl group of the sheath fiber undergo a dehydration condensation reaction to form amide bonds covalently, thus constructing a wear-resistant functional layer bonded by chemical covalent bonds on the fiber sheath surface. Washing and setting steps: After baking, the fabric is washed to remove unreacted free finishing agents, and then set to obtain the high abrasion-resistant polyester functional fabric.
2. The method for preparing a high abrasion-resistant polyester functional fabric according to claim 1, characterized in that: The skin material is prepared by the following method: using purified terephthalic acid and ethylene glycol as the main monomers, sodium dimethyl isophthalate-5-sulfonate at 3-8 mol% relative to the molar amount of purified terephthalic acid is added for transesterification. After transesterification, polyethylene glycol with a number average molecular weight of 600-2000 g / mol is added. The amount of polyethylene glycol added is 3-10 wt% of the theoretical yield of copolymerized polyethylene terephthalate. Then, melt polycondensation is carried out under an absolute pressure not exceeding 100 Pa and a temperature of 275-285 °C until the intrinsic viscosity of the skin material reaches 0.55-0.70 dL / g and the terminal hydroxyl content is not less than 30 mmol / kg.
3. The method for preparing a high abrasion-resistant polyester functional fabric according to claim 1, characterized in that: The core layer raw material is vacuum-dried at 130-140°C for no less than 6 hours before spinning, and the moisture content is controlled below 30ppm. In the composite spinning step, the core layer spinning box temperature is 290°C, the sheath spinning box temperature is 275-280°C, the nascent fiber is drawn by hot rollers, the pre-drawing roller temperature is 80-90°C, the main drawing roller temperature is 130-140°C, the total draw ratio is 3.0-4.5 times, the heat setting temperature is 200-210°C, and the setting time is 0.5-1.0s.
4. The method for preparing a high abrasion-resistant polyester functional fabric according to claim 1, characterized in that: In the low-temperature plasma pre-activation step, the discharge gas is air, the power density is 10-30 W / cm², the processing time is 30-120 s, the processing temperature is 25-40 °C, and the time interval between the end of the plasma pre-activation treatment and the padding finishing liquid does not exceed 30 min.
5. The method for preparing a high abrasion-resistant polyester functional fabric according to claim 1, characterized in that: The finishing solution comprises, by total mass, 2-5 wt% modified nano-silica with surface-grafted epoxy groups, 3-8 wt% polyetheramine with a number-average molecular weight of 600-2000 g / mol, 0.5-1.0 wt% nonionic penetrant, glacial acetic acid to adjust the pH of the finishing solution to 5.5-6.5, and the remainder being deionized water. The modified nano-silica is prepared by surface grafting modification of fumed silica with a particle size of 10-30 nm with 3-glycidyl etheroxypropyltrimethoxysilane, wherein the amount of 3-glycidyl etheroxypropyltrimethoxysilane is 5-10 wt% of the mass of fumed silica.
6. The method for preparing a high abrasion-resistant polyester functional fabric according to claim 1, characterized in that: The immersion and rolling step is carried out in a two-immersion and two-rolling manner, with a roll allowance of 65% to 80%, a roll pressure of 0.3 to 0.5 MPa, a finishing solution temperature of 20 to 40°C, and a pre-drying process at 80 to 100°C for 3 to 5 minutes.
7. The method for preparing a high abrasion-resistant polyester functional fabric according to claim 1, characterized in that: In the in-situ covalent bonding finishing step, modified nano-silica with surface-grafted isocyanate groups is used instead of modified nano-silica with surface-grafted epoxy groups. The modified nano-silica with surface-grafted isocyanate groups is prepared by surface grafting modification of fumed silica with a particle size of 10-30 nm with 3-isocyanate-propyltrimethoxysilane. The baking temperature is adjusted to 140-160℃. The isocyanate groups undergo urethane reaction with the terminal hydroxyl groups on the surface of the corrugated fiber to form urethane bonds for covalent bonding.
8. The method for preparing a high abrasion-resistant polyester functional fabric according to claim 1, characterized in that: In the weaving step, the fabric structure is twill weave, and the finished fabric weight is 180-350 g / m². The scouring step uses an alkaline scouring solution at 80-90℃ to remove spinning oil and impurities. In the washing and setting step, the washing temperature is 80℃, the washing is repeated at least three times, and the setting temperature is 170-180℃.
9. The high abrasion-resistant polyester functional fabric prepared by the preparation method according to any one of claims 1 to 7, characterized in that, The abrasion-resistant functional layer in the fabric is covalently bonded to the fiber skin layer. After 50 standard household washes, the abrasion resistance retention rate is no less than 85%, and the release of microplastics in the washing wastewater is reduced by no less than 70% compared with the comparative polyester fabric treated with polyurethane physical coating.